Policy Options for Low‐Carbon Power Generation in China Designing an Emissions Trading System for China's Electricity Sector - Baron, Richard (OECD Publishing, 2012)
China faces the dynamic of rapid economic development that drives ever increasing energy use, primarily electricity, and consequently increasing CO2 emissions. It has taken a pledge to curb its emissions intensity, and is exploring various policy approaches to fulfil that aim, including emissions trading. This report explores the conditions needed for effective functioning of a CO2 emissions trading system in China's electricity generation sector. It is based on extensive discussions with power generation stakeholders and observers of the electricity sector in China, as well as quantitative analyses of the impact of a CO2 emissions trading system (ETS) at plant, company and provincial levels
Keywords: Energy; China, People's Republic